Management of Technical Risk for the Ravensthorpe Nickel Project - D White; I Skepper; G Miller; R Fury (The Australasian Institute of Mining and Metallurgy, 2004)
Although the Pressure Acid Leaching (PAL) of nickel laterites has been conducted at Moa Bay, Cuba, since the early 1960s, the commissioning delays generally encountered by the æsecond generationÆ of PAL lateritic nickel producers in the late 1990s have demonstrated the potential complexity of the PAL process and the importance of technical risk management in maximising the realised project value. This paper describes some of the strategies used by the Ravensthorpe Nickel Project (RNP) to manage the technical aspects of the Ravensthorpe project risk. Central to these strategies is the use of Front End Loading (FEL) to deal with issues early in the development phase, when changes to the project structure can be made most effectively and cheaply. Such an approach requires a management philosophy that recognises risk as a potential cost, which accepts responsibility for dealing with risk, and which is prepared to provide adequate resources for risk management.